Reselling or marketplace mode for an online platform: the choice between cap-and-trade and carbon tax regulation - Yu, Yugang; Li, Xue; Xu, Xiaoping (Annals of operations research, 2022)
This paper explores a manufacturer’s production decisions and a government’s choice between cap-and-trade and carbon tax regulation. The manufacturer sells its product through offline and online channels, and we consider the online-offline spillover effect (OOSE) to reflect the influence of online sales on offline sales. We further compare carbon emission, the manufacturer’s profit, and social welfare for reselling and marketplace modes under the two types of regulations. First, we find that under both policies, when the government allocates a tight cap (high tax rate), the manufacturer should decrease online sales if the OOSE increases, and vice versa. Interestingly, we also discover that the manufacturer’s profit may decrease with the cap regardless of the modes. Second, under a low (high) environmental coefficient, the social welfare using reselling mode is lower (higher) than using marketplace mode, and the two modes can generate the same social welfare under a moderate environmental coefficient. Third, using either mode, when the environmental damage coefficient is low (high), the government should implement cap-and-trade regulation (carbon tax regulation). Finally, based on the data of a real-world company, when the environmental damage coefficient is low (high), the company should use an online platform with marketplace (reselling) mode to achieve optimal profit.